Optimal Timing for Oocyte Denudation and Intracytoplasmic Sperm Injection. (20th February 2012) - Patrat, Catherine; Kaffel, Aida; Delaroche, Lucie; Guibert, Juliette; Jouannet, Pierre; Epelboin, Sylvie; De Ziegler, Dominique; Wolf, Jean-Philippe; Fauque, Patricia
Abstract : Objectives . To analyze the impact of oocyte denudation and microinjection timings on intracytoplasmic sperm injection (ICSI) outcomes. Study Design . We included ICSI cycles with the following parameters: rank 1 or 2, female age < 36 years, male factor infertility, long protocol using GnRH agonist and rFSH for ovarian stimulation, and use of freshly ejaculated sperm (n = 110 ). Several ICSI parameters were analyzed according to the time between oocyte retrieval and denudation (T 1 ) and the time between denudation and ICSI (T 2 ) using a statistical logistic regression analysis. Results . Neither T 1 nor T 2 had a significant influence on the Metaphase II (MII) rate but the fertilisation rate (FR) showed a significant improvement when T 1 was longer (optimal results at T 1 = 3 hours) while FR significantly decreased with the increase of T 2 . Optimal implantation (IR) and pregnancy (PR) rates were obtained when T 1 was around 2 hours. Conclusion . Incubation of oocytes around 2 hours between retrieval and denudation may not increase MII rate but appears to lead to the optimal combination of FR and IR.